A Simple Macroeconomic Model of Decentralized Emission Markets Based on the Solow Growth Model - Zhang, Alfred Ruoxi; Zandi, Farrokh; Kim, Henry (Frontiers in Blockchain, 2020)
As technology revolutionizes the methods of both production and communication, economists have to respond to new market structures and efficiencies, and the controversial concept of decentralization emerging in recent decades should also be examined in terms of its capacity to induce structural changes in the economy. This paper takes look at one specific market of interest and models the decentralization of a hypothetical emission quota market with the inclusion of households though automated auctions, in order to provide a preliminary analysis of how the redistribution of emission quotas would impact short-run equilibrium in this market and long-run growths; Given the endogenous dynamics, we would also examine the effects of exogenous technological shocks, For the purpose and scope of this paper, a simple mathematical formulation based on the Solow growth model as well as certain strong assumptions derived from economic intuitions is established, aiming to provide a more quantitative illustration of the effects from decentralization on such a system.